2009
DOI: 10.2139/ssrn.1726742
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Health to Economic Development: A Survey and Overview

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 138 publications
(172 reference statements)
0
5
0
2
Order By: Relevance
“…Weakness in health and weakness in its promotional mechanisms have been associated with physical weakness, psychological problems hindering activity and production, poverty and ultimately reduced economic development [14]. On the other hand, it has been found that health and health care can lead to economic development and thus improve working conditions through higher productivity and more motivation of the workforce [5]. Can improving working conditions and ease of doing business also affect the health of communities?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakness in health and weakness in its promotional mechanisms have been associated with physical weakness, psychological problems hindering activity and production, poverty and ultimately reduced economic development [14]. On the other hand, it has been found that health and health care can lead to economic development and thus improve working conditions through higher productivity and more motivation of the workforce [5]. Can improving working conditions and ease of doing business also affect the health of communities?…”
Section: Discussionmentioning
confidence: 99%
“…Healthy people are encouraged to work less, have more life expectancy, have more fun, have less fatigue and have more motivation to do work, and as a result have more efficiency. People's health indirectly affects their easier learning, and this makes things happen faster and activities that lead to production and economic development accelerate [4,5]. On the other hand, the business situation in the communities can also be an explanatory factor for the health status of the communities.…”
Section: Introductionmentioning
confidence: 99%
“…Tingkat pendidikan, demografi, umur, dan pekerjaan. menganalisis bagaimana faktor-faktor tertentu terhadap pola konsumsi pelayanan kesehatan; tarif, subsidi, asuransi kesehatan, pendapatan, opportunity cost, dll (Husain, 2010).…”
Section: Konsep Permintaan Terhadap Pelayanan Kesehatanunclassified
“…The improvement of health services has a direct effect on the level of public health and an indirect effect on strengthening economic growth (Nishiura, 2004). Furthermore, public health levels can increase workforce productivity and per capita GDP (Akram, Padda & Khan, 2008), the quality of human capital and economic growth (Sharma, 2018 andMihalache, 2019), high productivity and income (Schultz, 2005;Weil, 2007;and Husain, 2010). Bloom, Canning & Sevilla (2001) stated that education, experience, and health are inputs of human capital.…”
Section: Introductionmentioning
confidence: 99%